Polypropylene composition as well as preparation method and application thereof
By controlling the overall crystallinity and optimized ratio of the polypropylene composition, the balance of gloss, appearance grades and material rigidity in the automotive interior field is solved, and the comprehensive performance of the material with low gloss, high rigidity and good appearance is achieved.
Patent Information
- Application Number
- CN202411876019.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-05-02
AI Technical Summary
The prior art is difficult to effectively balance the gloss, appearance grade and material rigidity of polypropylene materials, especially in the field of automotive interiors, which are difficult to meet the requirements for improving material quality.
By selecting a polypropylene resin with a certain crystallinity, the overall crystallinity of the polypropylene composition is controlled between 34.5% and 39.5%, combined with the ratio of composite polypropylene, toughener and talc powder, the melt flow rate and spherical crystal structure of the material are optimized, and a good balance of gloss, appearance grade and material rigidity is achieved.
The gloss of the polypropylene composition is reduced to less than 2.9, the bending modulus is maintained above 1500MPa, and it has high fluidity, avoiding the formation of tiger skin patterns and improving the appearance quality of the automotive interior parts.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of modified plastics, and specifically relates to a polypropylene composition and a preparation method and application thereof. Background Art
[0002] Polypropylene (PP) is a semi-crystalline thermoplastic with many excellent properties and a wide range of applications. Currently, polypropylene is widely used in automobiles, such as bumpers, door panels, pillars, dashboards, engine hoods, etc., playing an important role in the integration, lightweight, aesthetics, and comfort of automobiles.
[0003] In the automotive industry, especially in the field of automotive interior and exterior materials, modified polypropylene materials have a place due to their excellent processing performance and physical and chemical properties. Automotive polypropylene materials generally refer to composite materials with PP as the main component, usually containing toughening agents, talcum powder fillers, polyethylene and other functional additives. In recent years, people's requirements for the quality of automotive materials have been continuously improved, not only requiring products to have good intrinsic quality, but also paying great attention to the appearance of products. Common automotive interior materials such as dashboards and door panels are usually designed as leather grain surfaces to improve the texture of the interior. For automotive interior materials, the glossiness of the material surface is an important factor affecting the appearance. The increase in glossiness will increase the plastic feel of the material, which will reduce the overall appearance and grade of the car. On the other hand, with the design trend of thin-walled interior and exterior decoration and point gates, the frequency of abnormal appearance such as tiger skin grain and flow marks of some large injection molded parts is also higher, which puts higher requirements on modified plastic raw materials.
[0004] The prior art lacks a polypropylene composition formula that effectively balances the gloss texture, appearance grade and material rigidity of polypropylene products. Therefore, it is of great practical significance to develop a polypropylene composition material with lower gloss, good appearance and rigidity for application in the field of automotive interiors. Summary of the invention
[0005] The object of the present invention is to overcome the above technical problems and provide a polypropylene composition that effectively balances the gloss texture, appearance grade and material rigidity of the polypropylene composition.
[0006] Another object of the present invention is to provide a process for preparing the polypropylene composition.
[0007] Another object of the present invention is to provide application of the polypropylene composition.
[0008] The present invention is achieved through the following technical solutions: A polypropylene composition, characterized in that it comprises the following components in parts by weight: Composite polypropylene 60-87 parts; 3-10 parts of toughening agent; 10-30 parts of talcum powder; The composite polypropylene is composited from at least two single polypropylenes; The overall crystallinity of the polypropylene composition composed of composite polypropylene and toughening agent is K, wherein the crystallinity of any single polypropylene is recorded as α, and its proportion in the total number of parts of the polypropylene composition is recorded as β; wherein the crystallinity of any single toughening agent is recorded as γ, and its proportion in the total number of parts of the polypropylene composition is recorded as δ; then the overall crystallinity of the polypropylene composition K=(α1*β1+α2*β2+…+γ1*δ1+γ2*δ2…) / (β1+β2+…+δ1+δ2…); The overall crystallinity K of the polypropylene composition is 34.5% to 39.5%; The crystallinity of any single polypropylene constituting the composite polypropylene is 33%-43%, and is tested by DSC (differential scanning calorimetry) according to ASTM F2625-2010 standard; the test conditions are 30-200°C, nitrogen purging, heating to 200°C at a rate of 10°C / min and holding the temperature for 5min, then cooling to 30°C at the same rate and holding the temperature for 5min, and then heating for a second time, also at a rate of 10°C / min to 200°C, and calculating the crystallinity based on the second heating data.
[0009] The melt flow rate of any one of the polypropylenes is 16-60 g / 10 min, and the test conditions are a temperature of 230° C. and a test weight of 2.16 kg.
[0010] Selecting at least two single polypropylenes for compounding can make up for the deficiencies of a single type of polypropylene in certain aspects. Among the selected polypropylenes, one can provide advantages in rigidity and / or fluidity, and the other can provide good toughness. At the same time, by optimizing the crystallinity of the several polypropylenes, the material can be given excellent comprehensive properties.
[0011] The overall crystallinity K of the polypropylene composition affects both the gloss and the rigidity of the polypropylene composition.
[0012] When K is low, the glossiness of the material can be effectively reduced. The principle is that the lower the overall crystallinity of the resin substrate, the lower the proportion of regular parts of the molecular chain of the material, the less light flux reflected from the surface, and the lower the glossiness.
[0013] On the contrary, when the overall crystallinity K increases, the regular spherulite structure helps to improve the rigidity of the material, which is reflected in a significant increase in the value of the bending modulus.
[0014] Preferably, the above-mentioned polypropylene composition comprises the following components in parts by weight: Composite polypropylene 70-85 parts; 3-10 parts of toughening agent; 12-25 parts of talcum powder.
[0015] Preferably, the overall crystallinity K of the polypropylene composition is 36.5%-37.5%.
[0016] Preferably, the melt flow rate of any single polypropylene is 25-60 g / 10 min, and the test conditions are a temperature of 230° C. and a test weight of 2.16 kg.
[0017] When the melt flow rate of the polypropylene used is too low, although the gloss and rigidity of the polypropylene composition can be well balanced, the too low fluidity will cause tiger stripes to appear during injection molding, thus affecting the appearance of the product.
[0018] Preferably, the mesh size of the talcum powder is 1250-5000 mesh.
[0019] Preferably, the polypropylene is selected from copolymerized polypropylene.
[0020] Preferably, the toughening agent is selected from at least one of ethylene-butene copolymer and ethylene-octene copolymer.
[0021] Preferably, the melt flow index of the toughening agent is 3-15 g / 10 min, and the test conditions are a temperature of 190° C. and a test weight of 2.16 kg.
[0022] Preferably, based on weight fraction, 0.4-1 part of processing aid is also included.
[0023] Preferably, the processing aid is selected from at least one of hindered phenols or phosphites.
[0024] Preferably, the processing aid is selected from a combination of hindered phenols and phosphites, with a mass ratio of (1-2): (1-2).
[0025] Preferably, the melt flow rate of the polypropylene composition of the present invention is 25-35 g / 10 min, more preferably 25-31 g / 10 min.
[0026] The present invention also provides a method for preparing the polypropylene composition, comprising the following steps: weighing each component by weight, mixing uniformly to obtain a premix, adding the premix to the main feed port of a twin-screw extruder, melt-extruding, granulating and drying to obtain a polypropylene composition.
[0027] Preferably, the melt extrusion conditions of the twin-screw extruder are: zone one temperature 100-120°C, zone two temperature 190-210°C, zone three temperature 210-230°C, zone four temperature 210-230°C, zone five temperature 210-230°C, zone six temperature 210-230°C, zone seven temperature 210-230°C, zone eight temperature 210-230°C, zone nine temperature 210-230°C, main engine speed 250-600 rpm; the aspect ratio of the twin-screw extruder is 32:1-40:1.
[0028] The present invention also provides application of the polypropylene composition for preparing automotive interior decoration parts.
[0029] The present invention has the following beneficial effects: The present invention provides a polypropylene composition that can be used for automotive interior parts. By selecting a polypropylene resin with a certain degree of crystallinity, the overall crystallinity of the polypropylene composition is controlled within an appropriate range, and the gloss and rigidity of the material can achieve a good balance. According to experimental tests, the gloss of the polypropylene composition provided by the present invention can be reduced to below 2.9, the bending modulus is maintained above 1500MPa, and the high fluidity (MFR≥25) can make the injection molded product have a good appearance and avoid the formation of tiger stripes.
[0030] The invention defines the concept of the overall crystallinity K of the polypropylene composition, realizes the effective characterization of the crystallinity of the high molecular weight part in the modified polypropylene, and reveals the relationship between the overall crystallinity of the polypropylene composition and the gloss and rigidity. DETAILED DESCRIPTION
[0031] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0032] The raw materials used in the present invention come from: Polypropylene 1: PP EP548RQ produced by Sinopec, with a melt flow rate of 28 g / 10 min at 230 °C and 2.16 kg load according to ISO 1133-1:2022, and a crystallinity of 41.6%; Polypropylene 2: PP K9829H produced by Yanshan Petrochemical, according to ISO 1133-1:2022, at 230°C, 2.16kg load, the melt flow rate is 28g / 10min, and the crystallinity is 33.1%; Polypropylene 3: PP EP5075X produced by Sinopec, with a melt flow rate of 60 g / 10 min at 230 °C and 2.16 kg load according to ISO 1133-1:2022, and a crystallinity of 42.8%; Polypropylene 4: PP SP179 produced by Lanzhou Petrochemical, with a melt flow rate of 10 g / 10 min at 230 °C and a load of 2.16 kg according to ISO 1133-1:2022, and a crystallinity of 35.2%; Polypropylene 5: BX3900 produced by SK, South Korea, according to ISO 1133-1:2022, at 230 ° C, 2.16 kg load, the melt flow rate is 55 g / 10 min, and the crystallinity is 45.4%; Polypropylene 6: BX3800 produced by SK, South Korea, according to ISO 1133-1:2022, at 230 ° C, 2.16 kg load, the melt flow rate is 28 g / 10 min, and the crystallinity is 42.8%; Toughener 1: ethylene-butene copolymer, Dow Chemical POE ENGAGE 7447, crystallinity 13%; Toughener 2: ethylene-octene copolymer, Dow Chemical POE ENGAGE 8207, crystallinity 19%; Talc: commercially available 3000 mesh talc; Processing aid 1: hindered phenol, antioxidant 1010; Processing aid 2: phosphite, antioxidant 168.
[0033] Various test methods: (1) Gloss test: The prepared polypropylene composition was dried and injection molded into a small leather grain plate of 60 mm*80 mm*2 mm. The glossiness of the sample was tested at an angle of 60° using a gloss meter and the values were recorded.
[0034] (2) Appearance inspection: The prepared polypropylene composition was injection molded into a flat combustion plate of uniform thickness of 360 mm*100 mm*3 mm at a temperature of 200-230°C. The appearance was rated by examining the tiger skin pattern on the surface. The appearance grades are as follows: Grade 1: no tiger skin pattern visible at any angle; Grade 2: tiger skin pattern vaguely visible; Grade 3: tiger skin pattern clearly visible at any angle.
[0035] (3) Flexural modulus: The flexural modulus of the tested material was tested using the ISO 178-2019 standard, with a temperature of 23°C, a span of 64 mm, and a bending speed of 2 mm / min.
[0036] (4) Melt flow rate: The melt flow rate of the polypropylene composition was tested at 230°C and a load of 2.16 kg using ISO 1133-1:2022.
[0037] (5) Crystallinity of single polypropylene: The test was conducted using the DSC method (differential scanning calorimetry) according to ASTM F2625-2010. The test conditions were 30-200°C, nitrogen purging, heating at a rate of 10°C / min to 200°C and holding the temperature for 5 min, then cooling at the same rate to 30°C and holding the temperature for 5 min, and then heating for a second time, also at a rate of 10°C / min to 200°C. The crystallinity was calculated based on the data from the second heating.
[0038] (6) Overall crystallinity: The crystallinity of a single polypropylene is denoted as α, and its proportion in the total is denoted as β; the crystallinity of a single toughening agent is denoted as γ, and its proportion in the total is denoted as δ; then the overall crystallinity of the polypropylene composition K = (α1*β1+α2*β2+…+γ1*δ1+γ2*δ2…) / (β1+β2+…+δ1+δ2…).
[0039] The preparation process of the embodiments and comparative examples of the present invention is as follows: Weigh each component according to the weight portion of each embodiment and comparative example, put it into a high-speed mixer for high-speed mixing for 3 minutes, add the premix after uniform mixing to the main feeding port of the twin-screw extruder, perform melt extrusion, granulate and dry, and obtain the organic solvent-resistant polypropylene material. The melt extrusion conditions of the twin-screw extruder are: the temperature of the first zone is 120°C, the temperature of the second zone is 190°C, the temperature of the third zone is 210°C, the temperature of the fourth zone is 210°C, the temperature of the fifth zone is 210°C, the temperature of the sixth zone is 230°C, the temperature of the seventh zone is 230°C, the temperature of the eighth zone is 230°C, the temperature of the ninth zone is 230°C, and the main engine speed is 350 rpm; the aspect ratio of the twin-screw extruder is 40:1.
[0040] Table 1 Weight parts of each component of polypropylene composition of Examples 1-6 and Comparative Examples 1-3
[0041] Table 2 Performance test results of polypropylene compositions of Examples 1-6 and Comparative Examples 1-3
[0042] It can be seen from Examples 1-6 that the glossiness of the polypropylene composition prepared by the present invention is lower than 2.90, the appearance grade is 1, and the bending modulus is maintained above 1500 MPa, which ensures the low gloss texture of the polypropylene composition while maintaining a high appearance grade and material rigidity.
[0043] The overall crystallinity of the polypropylene composition in Comparative Example 1 is relatively low, and the flexural modulus is also relatively low.
[0044] The overall crystallinity of the polypropylene composition in Comparative Example 2 is relatively high. Although the polypropylene composition has a relatively high bending modulus, the glossiness is also increased to 3.5, and a low-gloss texture cannot be provided.
[0045] The overall crystallinity of the polypropylene composition in Comparative Example 3 is within an appropriate range, but the melt flow rate of the single polypropylene used is relatively low, resulting in a low melt flow rate of the polypropylene composition. The excessively low fluidity causes tiger skin pattern phenomenon during injection molding, thereby affecting the appearance of the product.
[0046] The melt flow rate of the polypropylene composition in Comparative Example 4 is between that of Examples 1-2, but the overall crystallinity of the polypropylene composition is higher than that of Examples 1-2, and the value is close to that of Comparative Example 2. Its performance test results are also close to those of Comparative Example 2. Although the polypropylene composition has a higher flexural modulus, the glossiness is increased to 3.25, and a low gloss texture cannot be provided.
Claims
1. A polypropylene composition, characterized in that According to weight parts, it includes the following components: 60-87 parts of composite polypropylene; 3-10 parts of toughening agent; 10-30 parts of talcum powder; The composite polypropylene is composited from at least two single polypropylenes; The overall crystallinity of the polypropylene composition is 34.5%-39.5%; The crystallinity of any single polypropylene constituting the composite polypropylene is 33%-43%; The melt flow rate of any single polypropylene is 16-60 g / 10 min, and the test conditions are a temperature of 230° C. and a test weight of 2.16 kg.
2. The polypropylene composition according to claim 1, characterized in that The overall crystallinity of the polypropylene composition is 36.5%-37.5%.
3. The polypropylene composition according to claim 1, characterized in that The melt flow rate of any single polypropylene is 25-60 g / 10 min, and the test conditions are a temperature of 230° C. and a test weight of 2.16 kg.
4. The polypropylene composition according to claim 1, characterized in that The toughening agent is selected from at least one of ethylene-butene copolymer and ethylene-octene copolymer.
5. The polypropylene composition according to claim 1, characterized in that By weight, 0.4-1 part of processing aid is also included.
6. The polypropylene composition according to claim 5, characterized in that The processing aid is selected from at least one of hindered phenols and phosphites.
7. The polypropylene composition according to claim 6, characterized in that The processing aid is selected from a combination of hindered phenols and phosphites, with a mass ratio of (1-2): (1-2).
8. The method for preparing the polypropylene composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: The components are weighed in parts by weight, mixed evenly to obtain a premix, which is then added to a main feed port of a twin-screw extruder, melt-extruded, granulated and dried to obtain a polypropylene composition.
9. The method for preparing a polypropylene composition according to claim 8, characterized in that: The melt extrusion conditions of the twin-screw extruder are: temperature of zone 1 is 100-120°C, temperature of zone 2 is 190-210°C, temperature of zone 3 is 210-230°C, temperature of zone 4 is 210-230°C, temperature of zone 5 is 210-230°C, temperature of zone 6 is 210-230°C, temperature of zone 7 is 210-230°C, temperature of zone 8 is 210-230°C, temperature of zone 9 is 210-230°C, and main engine speed is 250-600 rpm; the aspect ratio of the twin-screw extruder is 32:1-40:
1.
10. Use of the polypropylene composition according to any one of claims 1 to 7, characterized in that: Used to prepare automotive interior parts.
Citation Information
Cited By
Polypropylene compound, and preparation method therefor and use thereof
WO2026129982A1